THE ASSOCIATION BETWEEN FAMILY FUNCTION AND CHILD BEHAVIOUR AND ITS RELATIONSHIP WITH EXPENDITURES FOR USE OF HEALTH AND SOCIAL SERVICES AMONG CHILDREN/YOUTH WHO SURVIVE TRAUMA - Garnett, Anna (My University, 2012)
To date most research on long-term outcomes of childhood trauma has focused on traumatic brain injuries, but less is known about traumatic injuries not involving the brain. Since traumatic brain injuries can have persistent effects on child behaviour, I investigated whether other types of traumatic injuries could also affect child behaviour in the long term. Currently, limited information is available on possible associations between family function and child behaviour after child trauma; knowledge of the long-term costs of pediatric trauma is also lacking. The main goal of this study was to determine whether family function was associated with behaviour in children who experienced a traumatic injury eight to ten years ago. Additional goals were to determine current expenditures and use of health and social services by child trauma victims and their parents. Pediatric trauma victims were selected from a trauma database at a tertiary care hospital in the Hamilton-Wentworth region. The parents of these children were interviewed to obtain children’s current behaviours and the family’s use of health and social services. The results showed that injury severity was not associated with child behaviour, but associated with family functioning. No relationship was found between health and social service expenditures for children and their injury severity, but there was a relationship between parent health and social service expenditures and child injury severity. The results do not support an association between child behaviour and injury severity following trauma, but they do suggest that expenditures and use of services by injured children and their families are affected long-term. The results suggest that future health and social service uses of injured children and their families may be better understood and planned for by recognizing the continuing effects of trauma. This information could help making appropriate health and social service programs more available to this population.
Keywords: Trauma; children; family function; child behaviour; Family Practice Nursing; Other Nursing; Pediatric Nursing; Family Practice Nursing